Diagnostic Exercise: Poor Performance in a Racehorse. (July 2014) - Giannitti, F.; Petrov, R.; Parker, J.; Booth, M.; Anderson, M.
A 9-year-old Thoroughbred gelding presented with a 97-day history of poor performance and intermittent fever. Clinicopathologic changes included increased serum activity of γ-glutamyltransferase and alkaline phosphatase, mild hyperbilirubinemia, and leukocytosis with neutrophilia and lymphopenia. Abdominal ultrasound revealed hepatomegaly with hyperechoic hepatic parenchyma and biliary distention. Pathologic findings included marked hepatomegaly (liver 3.6% of body weight), firm hepatic consistency with a diffuse enhanced reticular pattern, severe portal bridging and sinusoidal fibrosis, oval cell/bile duct hyperplasia, and bile stasis. The differential diagnoses and diagnostic workup to achieve the diagnosis are briefly discussed.